Viscoelastic,compatibility and morphological study of rubber adhesives. - Poh , Beng Teik (Universiti Sains Malaysia, 2016)
Loop tack, peel strength, shear strength, and morphology of (benzoyl peroxide)-cured epoxidized natural rubber (ENR 25)/(acrylonitrile-butadiene) rubber (NBR) blend adhesive were investigated by using petro resin as the tackifying resin.